When curiosity gaps backfire: effects of headline concreteness on information selection decisions - Marianne Aubin Le Quéré; J. Nathan Matias (Scientific Reports)
Abstract The selection of information by individuals is a basic process in democratic institutions, including journalism. Publishers attempt to attract readers with “curiosity gap” headlines that offer vague descriptions rather than summarize an article. Lab and field experiments that compare the influence of these two styles have found conflicting results on their efficacy. In this registered report, we propose a theory, based on the psychology of curiosity, to harmonize these results. We introduce and validate an automated linear scale of headline concreteness to differentiate summary and curiosity gap headlines. In a meta-analysis of 8977 headline experiments, we confirm that the effects of headline concreteness on clickthrough rates vary with the overall concreteness of other headlines. When the baseline headline is too vague, higher headline concreteness increases clickthrough rates. When headlines are too concrete, higher headline concreteness decreases clickthrough rates. These findings suggest a curvilinear relationship between information selection decisions and the amount of information conveyed in text, implying that headlines that convey just the right amount of information maximize clickthrough rates at scale. Protocol registration The protocol for this study was pre-registered following in-principle acceptance at https://osf.io/fbzvw/ on September 21st, 2023. The stage 1 protocol for this Registered Report was accepted in principle on 30/08/23. The protocol, as accepted by the journal, can be found at: https://doi.org/10.17605/OSF.IO/FBZVW .